Genetic variability of the fifth generation of nile tilapia Oreochromis niloticus using microsatellite DNA markers - Gloria Ika Satriani; Dinar Tri Soelistyowati; Dian Hardianto; Ratu Siti Aliah (Jurnal Akuakultur Indonesia)
ABSTRACT